Moth Diversity at Sebangau Peat Swamp and Busang River Secondary Rain Forest, Central Kalimantan - HARI SUTRISNO (Bogor Agricultural University, Indonesia, 2005)
A study on the diversity of moths was conducted from July to Augustus 2004 at the peat swamp forest Setya Alam research station, Sebangau, Central Kalimantan. The result showed that diversity of moths at this area was lower (100 species of 12 families; H = 6.643, E = 0.794) than that in secondary rain forest Busang River (278 species of 19 families; H = 8.139, E = 0.831). The result also showed that the similarity index (Cj) of the two areas was very low (0.05). Geometridae, Noctuidae, and Pyralidae were dominant in both areas. There might be more species that have not been found during eight night sampling as indicated by the species numbers in both areas has not reach a plateau.